Synthesis of Cardanil Methyl Ether via Etherification Reaction Cardanol Isolated from Cashew Nut Shells (Anacardium occidentale L.) with Variations of Molar Methyl Iodide - Sabarmin Perangin-angin; Riris Natalia Siburian (Journal of Chemical Natural Resources, 2023)
The synthesis of the Cardanyl methyl ether is carried out through an etherization reaction between Cardanyl seed skin extract (CNSL) isolated from the methyl iodide. Cardanol is isolated with the addition of acetone, Ca(OH)2, NH4OH 25%, n-hexane: ethyl acetate (98:2), washing with NaOH 2.5%, HCl 5%, aquadest, and Na2SO4 anhydrate. The yield of the obtained cardanol is 74.39 g (74.39% of the initial weight of the CNSL) and has the following characteristics: acid count 1.2863 mgKOH/g, iodine count 215.6535 g I2/100 g, viscosity 38.7 cP, density 0.8266 g/mL, pH = 6.14. The FT-IR methyl ether Cardanyl spectrum shows an absorption band at 1162.9-1259.8 cm-1 shows a C-O stretching group at a wave number of 1043.6-1148.0 cm-1 showing the formation of an asymmetric and symmetrical C- O-C stretching band of the ether compound, the Spectra of the FT - IR methyl ether Cardanyl shows an absorptive band at 1162-1259-125,8 cm-1, showing a C-O stretching Group, at the wave number of 1043.6-1148.0 cm-1 indicating the formation, as a result, of an Asymmetric and Symmetric Stretching Group of the ethereal Compound. The Cardanyl methyl ether was synthesized by adding K2CO3, the solvent acetone and the iodide-methyl, with a reflux time of 8 hours. As for the parameters carried out in this study, the molar variation of the Cardanyl is the Methyl Iodide (1:1.5, 1:3, and 1:4.5) and yields 3.555 g; 12.084 g; 11.472 g of Cardanyl ether. Methyl ether Cardanyl was obtained in analysis with FT-IR and GC-MS spectroscopic photometers. The results of the analysis of Cardanyl methyl ethers with GC -MS were 63.28%, and the results of analysis of the Cardanyl ether with a variation of the molar ratio Cardanyl: Methyl iodide (1:1.5; 1:3; 1:4.5) with GC-MS obtaining 3.05%, 30.29%, and 26.58%. These results show the maximum percentage of methyl ethers Cardanyl at the reaction conditions of the variation molar ratios Cardanyl iodides (1:3), K2CO3 17.3 g, 50 mL of acetone, and 8 hours of reflux time.